Fear, Stress, and Knowledge regarding COVID-19 in Nursing Students and Recent Graduates in Mexico - Isai Arturo Medina Fernández; Sonia Carreño Moreno; Lorena Chaparro Díaz; Ruth Magdalena Gallegos-Torres; Josué Arturo Medina Fernández; Eva Kerena Hernández Martínez (Universidad de Antioquia, 2021)
Objective. The study sought to correlate fear, stress, knowledge regarding COVID-19 in Nursing students and recent graduates in Mexico. Methods. Correlational design, sample comprising 912 nursing students and graduates during the last 18 months from public and private universities of Mexico. To measure the variables, the study applied the instrument Fear of COVID-19 Scale, knowledge subscale of the scale Knowledge, attitudes, and practices towards COVID-19, and the instrument COVID Stress Scale. Results. Relationship was found of the age variable with fear, danger of contamination, traumatic stress, knowledge and minor socioeconomic consequences (p<0.05). Likewise, relationship was observed of fear with stress regarding COVID-19, danger of contamination, socioeconomic consequences, xenophobia, traumatic stress, and compulsive checking (p<0.05). Stress and knowledge explain the presence of fear regarding COVID-19 in 50.3%, and fear and knowledge explain stress regarding COVID-19 in 50.4%. Conclusion. Nursing students and recent graduates have high levels of stress and fear, besides low level of knowledge. The presence of high stress and low knowledge predict fear regarding COVID-19. Interventions are required on knowledge, stress, and fear regarding COVID-19 in the population studied.